UPAYA MENINGKATKAN PROMOSI WISATA MELALUI PEMBUATAN MEDIA PROMOSI DIGITAL DI KAMPUNG WISATA KETANDAN - Umul Khasanah; Cahyabayu Dimas Yudha Pratama; Firlita Firlita; Kelvin Surya Saputra (Bajang Institute, 2024)
In 2016, the Surabaya city government named Ketandan village in Genteng sub-district a tourist village. Local and foreign tourists often conduct tours in Ketandan Village. However, until now there is still no concrete guidance on the route or points of interest in the village. Therefore, in this Real Work Lecture activity in collaboration with Akita University of Art, promotional media was created. The method used was to observe the attractions in Ketandan village, then take photos and mark them which would later be incorporated into digital promotional media. This activity succeeded in creating a multilingual (Indonesian-English-Japanese) tourist pamphlet, a bilingual (Indonesian-English) tourist catalog, and a three-minute Ketandan promotional video. These three promotional media are expected to help both the village management, youth organization, and tourism awareness group as well as tourists who come to visit Ketandan village. Furthermore, the Ketandan community can develop other promotional media.